2011
DOI: 10.5586/asbp.2006.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and genetic diversity of mistletoe (Viscum album L.) subspecies

Abstract: Viscum album L.) most frequently occurring in Poland, the common mistletoe living on deciduous trees; (2) Viscum album ssp. abietis (Wiesb.) Abromeit (= Viscum ABSTRACT With the help of 21 putative isoenzyme loci, the genetic diversity and variations of Viscum album ssp. album L. from 42 species, subspecies, varieties and hybrids of broadleaf trees, Viscum album ssp. austriacum (Wiesb.) Vollmann, from 4 populations of Scots pine (Pinus sylvestris L.) and Viscum album ssp. abietis (Wiesb.) Abromeit, from 8 popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…This would be a return to earlier concepts in which mistletoe occurring on pine trees was referred to as Viscum laxum Boiss, while mistletoe occurring on trees from the genus Abies was referred to as Viscum abietis Beck. 25 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This would be a return to earlier concepts in which mistletoe occurring on pine trees was referred to as Viscum laxum Boiss, while mistletoe occurring on trees from the genus Abies was referred to as Viscum abietis Beck. 25 , 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of two other mistletoe species have reported similar or lower levels of genetic variability. For example, Jerome and Ford (2002) used AFLP markers to detect genetic diversity of Arceuthobium americanum ( H T = 0.238, F ST = 0.286), and Mejnartowicz (2006) used isozymes to study Viscum album ( H O = 0.252, H E = 0.292, F ST = 0.277). The higher degree of population genetic differentiation among the D. pentandra populations may be the result of habitat fragmentation, as reported in studies of other plants (e.g., Ewers & Didham, 2006; Potts et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of subspecies are recognised, treated as forms, varieties or even species by some (Mejnartowicz, 2006). Subspecies album L. (= var.…”
mentioning
confidence: 99%